2008
DOI: 10.1155/2008/763654
|View full text |Cite
|
Sign up to set email alerts
|

Third‐Body Perturbation in the Case of Elliptic Orbits for the Disturbing Body

Abstract: This work presents a semi-analytical and numerical study of the perturbation caused in a spacecraft by a third-body using a double averaged analytical model with the disturbing function expanded in Legendre polynomials up to the second order. The important reason for this procedure is to eliminate terms due to the short periodic motion of the spacecraft and to show smooth curves for the evolution of the mean orbital elements for a long-time period. The aim of this study is to calculate the effect of lunar pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 10 publications
1
47
1
Order By: Relevance
“…Similar computations as in [7] will lead to more accurate model useful with longer time transfers. Finally the lunar perturbation and the J 2 -effect can be superposed and their effects numerically analysed for space mission where both effects have to be taken into account.…”
Section: Extensionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar computations as in [7] will lead to more accurate model useful with longer time transfers. Finally the lunar perturbation and the J 2 -effect can be superposed and their effects numerically analysed for space mission where both effects have to be taken into account.…”
Section: Extensionsmentioning
confidence: 86%
“…(see [7] for more precise expansions). A simplified academic model is to set the eccentricity ρ to zero, the inclination i to zero and to restrict the control to this plane, the lunar perturbing potential becomes…”
Section: Development Of the Term Cosmentioning
confidence: 99%
“…Costa & Prado (2002) discussed the critical angle of a third-body perturbation that is a value for the inclination such that any near-circular orbit with inclination below this value remains near-circular. Domingos et al (2008) showed an analytical expansion to study the third-body perturbation for a case where the perturbing body is in an elliptical orbit, based on the expansion of the perturbing function in polynomials of Legendre.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the study done by Broucke (2003), Prado (2003) and Domingos et al (2008) is expanded, including the eccentricity and inclination of the perturbing body. A three-dimensional model is used to study the effects of a third-body gravitational potential on the spacecraft that orbits near a celestial body including the eccentricity and the inclination of the third-body in the formulation.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we can cite the Jupiter Europa Orbiter (JEO, NASA) and the Jupiter IcyMoon Explorer (JUICE, ESA). Several papers have contributed to a better understanding of the dynamics involved in this type of mission (see for example Scheeres et al, 2001;Prado, 2003;Paskowitz & Scheeres, 2005a, 2005b Lara & Russel, 2006, 2007Domingos et al, 2008;Carvalho et al, 2010 Carvalho et al, , 2012a Carvalho et al, , 2012bLiu et al, 2012). The study performed in this paper is related to the orbital motion of artificial satellites around Europa considering polygenic perturbations due to its non-spherical shape and the third-body perturbation due to Jupiter.…”
mentioning
confidence: 99%